Polyethylene glycol-coated zinc oxide nanoparticle: an efficient nanoweapon to fight against herpes simplex virus type 1. (22nd October 2018) - Tavakoli, Ahmad; Ataei-Pirkooh, Angila; MM Sadeghi, Gity; Bokharaei-Salim, Farah; Sahrapour, Peyman; Kiani, Seyed J; Moghoofei, Mohsen; Farahmand, Mohammad; Javanmard, Davod; Monavari, Seyed H
Aim: We aimed to determine the possible inhibitory effects of zinc oxide nanoparticles (ZnO–NPs) and polyethylene glycol (PEG)-coated ZnO–NPs (ZnO–PEG–NPs) on herpes simplex virus type 1 (HSV-1).Materials & methods: PEGylated ZnO–NPs were synthesized by the mechanical method. Antiviral activity was assessed by 50% tissue culture infectious dose (TCID50 ) and real-time PCR assays. To confirm the antiviral activity of ZnO–NPs on expression of HSV-1 antigens, indirect immunofluorescence assay was also conducted.Results: 200 μg/ml ZnO–PEG–NPs could result in 2.5 log10 TCID50 reduction in virus titer, with inhibition rate of approximately 92% in copy number of HSV-1 genomic DNA.Conclusion: ZnO–PEG–NPs could be proposed as a new agent for efficient HSV-1 inhibition. Our results indicated that PEGylation is effective in reducing cytotoxicity and increasing antiviral activity of nanoparticles.